Spartalizumab in combination with platinum-doublet chemotherapy with or without canakinumab in patients with PD-L1-unselected, metastatic NSCLC - Armando Santoro; Garrido Pilar; Daniel S.W. Tan; Jon Zugazagoitia; Frances A. Shepherd; Alessandra Bearz; Fabrice Barlesi; Tae Min Kim; Tobias R. Overbeck; Enriqueta Felip; Can Cai; Simantini Eddy; et al. (BMC Cancer)
Abstract Background Despite promising outcomes of treatment with anti-programmed cell death (PD)-1/PD-ligand (L)1 agents in combination with platinum-doublet chemotherapy (PDC) in the first-line setting, a significant unmet medical need remains in patients with PD-L1-unselected non-small cell lung cancer (NSCLC). Methods This multicenter, open-label, phase 1b study comprising dose-confirmation and dose-expansion parts investigated the combination of spartalizumab and various PDC regimens, with or without canakinumab, in treatment-naïve patients with PD-L1-unselected, metastatic NSCLC. The primary objectives were to determine maximum tolerated dose (MTD) and/or recommended dose for expansion (RDE) of spartalizumab, with or without canakinumab, in combination with PDC in the dose-confirmation part and antitumor activity of spartalizumab in the dose-expansion part. Results The MTD/RDE of spartalizumab was 300 mg every 3 weeks (Q3W) when administered with either gemcitabine (1250 mg/m2)/cisplatin (75 mg/m2) (group A; no dose-limiting toxicities [DLTs]), pemetrexed (500 mg/m2)/cisplatin (group B; 2 DLTs: grade 2 posterior reversible encephalopathy syndrome and grade 4 hyponatremia), or paclitaxel (200 mg/m2)/carboplatin area under the curve 6 min*mg/mL (group C; 1 DLT: grade 4 neutropenic colitis). The RDE of canakinumab combined with spartalizumab and pemetrexed/cisplatin (group E; no DLTs) was 200 mg Q3W (no dose-expansion part was initiated). No new safety signals were identified. In groups A, B, C, and E, the overall response rates were 57.6%, 55.3%, 51.5%, and 57.1%, respectively. Group B compared with other groups had the longest median progression-free survival (10.4 months vs. 6.2–7.5 months), overall survival (29.7 months vs. 16.1–21.0 months), and duration of response (30.1 months vs. 6.0-8.2 months). Conclusions The combination of spartalizumab and PDC, with or without canakinumab, was well tolerated across treatment groups. The antitumor activity across treatment groups was comparable with that of pembrolizumab and pemetrexed combination. Canakinumab did not appear to improve the antitumor activity when combined with spartalizumab, pemetrexed and cisplatin. Trial registration The trial was registered in Clinicaltrials.gov with identifier no. NCT03064854. Date of Registration: 06 February 2017.